MALAY CULTURAL PRACTICE AND CHILDBIRTH WITH TRADITIONAL BIRTH ATTENDANTS: A QUALITATIVE STUDY IN WOMEN OF PRODUCTIVE AGE IN WEST BORNEO INDONESIA - Lilis Lestari; Ramadhaniyati Ramadhaniyati (Belitung Raya Foundation, Indonesia, 2019)
Background: The decline in Maternal Mortality Rate (MMR) in developing countries still does not meet the target of Sustainable Development Goals (SDGs). The rise of childbirth with the help of traditional birth attendants and cultural practices still becomes the choice of women of productive age to give birth today. Objective: This study aimed to explore the Malay culture practice and childbirth with traditional birth attendants in women of productive age in West Borneo, Indonesia. Methods: This was a phenomenological study conducted on in 2018 in one district in West Borneo. Focus Group Discussion (FDG) was done with eight Malay tribal women who had given birth with the help of Traditional Birth Attendants (TBAs). Thematic analysis was used. Results: Cultural practices during pregnancy, childbirth and the care of newborns, the services of TBAs, and the economy factor were strong reasons for mothers to choose to give birth assisted by TBAs although they were aware of the risks. This study identified five main themes, namely: 1) Reason for choosing TBAs, 2) TBAs’ service, 3) Cultural trust in pregnancy, 4) Cultural trust in labor, and 5) Cultural trust in caring for newborns. Conclusion: Our findings revealed that culture and childbirth cannot be separated. Health practitioners should have different approach by involving culture and TBAs in childbirth among women of productive age in West Borneo Indonesia.